Violence Exposure and Support for State Use of Force in a Non-Democracy. Issue 2 (4th December 2018) - Hou, Yue; Quek, Kai
Abstract: How do individuals respond to internal security threats in non-democracies? Does violence make individuals more supportive of a strong state? Are the effects of violence on individual attitudes uniform, or are they heterogeneous with respect to the identity of the perpetrators? We field an online survey experiment on a national sample of Chinese citizens, in which respondents were randomly selected to view reports on violent acts in China. We show that exposure to violence makes individuals more supportive of a strong state: respondents randomly exposed to violence are more likely to approve police use of lethal force, and this effect is particularly strong among the less wealthy Han Chinese. We also find suggestive evidence that individuals exhibit intergroup biases in their reaction to violence.